Workforce Diversity and Organizational Effectiveness in 21st Century Business Arena - Yahaya, Ibrahim; Mato, Umar (Asian Accounting and Auditing Advancement, 2017)
The paper critically examines workforce diversity and its effect on organizational efficiency which has become the concern of the business environment in the present globalized business Arena in the 21st century, the objectives examined the recognition of workforce diversity by organizations, the anatomy of workforce diversity, and extent of organizational workforce diversity, the researched was based on secondary data and the findings are organizations in 21st century realized and committed to workforce diversity and it concluded for business competitive advantage, strategic workforce diversity is required in the globalized organization, and its recommended the high degree of leadership and managerial commitment in action for workforce diversity.